Hediste diversicolor sensu Hartmann-Schroder 1996 - Salazar-Vallejo, Sergio I.; León-González, Jesús Angel De; Conde-Vela, Víctor M. (Zenodo, 2021)
Hediste diversicolor (Müller, 1776) Nereis diversicolor Müller, 1776: 217 Nereis diversicolor – Örsted 1843: 23, figs 66, 68, 73. — Müller 1800: 104–118, pl. 6 figs 1–6. — McIntosh 1910: 312–324. — Heinen 1911: 46–49. — Fauvel 1923: 344, fig. 133a–f. — Chambers & Garwood 1992: 28–31, fig. 41. Hediste diversicolor – Malmgren 1867: 165–166, pl. 28 fig. 28. — Bakken 2004: 34–35, fig. 1 1. Nereis ( Hediste ) diversicolor – von Marenzeller 1874: 466–469, pl. 7 fig. 3. — Hartmann-Schröder 1996: 201–204, fig. 88. Remarks The taxonomic history of Hediste diversicolor is rather complex and has not been fully resolved. The original description was “body subdepressed, parapodia tapered with chaetae” (Müller 1776: 217), and no Greenlandic name or type locality was indicated; after invoking the ICZN, the Commission has moved to conclude that “the type locality has not been clarified” (Oug et al . 2014: 220). However, recommendation 76A1.3 is to take into account “the original description of the taxon”. The second line for the original description includes two references: “Würm. 104, t. 6, Str. S. 1, p. 198, 2?” The first is a previous paper by the author (Müller 1771), whereas the latter is a paper: “Physik og oeconomisk Beskrievelse over fogderiet Söndmör” by Hans Ström (published in Soröe [Sorø, Denmark] in 1762). We could not find the latter, but we found two editions of the former which contain an extended description (Müller 1771: 102–111, pl. 6 figs 1–6) and indications that the specimens were collected in Copenhagen. This information complies with the recommendation, and consequently the type locality should be Copenhagen, Denmark. It was reiterated in the second edition (Müller 1880: 110). Furthermore, specimens identified as H. diversicolor from the Baltic Sea include at least two different species, and this has complicated solving what we should regard as this biological species (Virgilio et al . 2009; Tosuji et al . 2019). Örsted (1843: 23) provided a description of Nereis diversicolor and included ...